Capua, Italien: Das Amphitheater - Beste, Heinz-Jürgen (e-Forschungsberichte des DAI, 2023)
Starting point of the project in collaboration with the Soprintendeza of Capua and Pozzuoli is specifically architectural research. Besides analysing the rich marble decoration in the interior, the study aims at clarifying the use of the basement and comparing it to that of the Colosseum. Hence, in addition to contributing to the knowledge of amphitheatres in general, the study is also related to an important aspect of the history of ancient technology.